The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0103-97332004000500024
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability and Cesium-137 inventories in native forest

Abstract: With the nuclear fi ssion discovery and development of nuclear weapons in 1940s, artifi cial radioisotopes were introduced in the environment. This contamination is due to worldwide fallout by superfi cial nuclear tests realized from early 1950s to late 1970s by USA, former URSS, UK, France and China. One of theses radioisotopes that have been very studied is cesium-137. Cesium-137 has a half-life of 30.2 years and its biological behavior is similar to the potassium. The behavior in soil matrix, depth distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
8
0
2
Order By: Relevance
“…A probable explanation for the higher values and the relatively stronger contamination of D2 in these plots could be the influence of soil micro-and mesoflora and micro-and mesofauna, erosion processes (Andrello and Appoloni, 2004) or differences in the initial cesium contamination before Chernobyl due to other sources. If we observe the plots from Central Balkan the tendencies in cesium profiles in plots PB1 and PB2 are quite similar and the content of cesium decreases clearly in depth.…”
Section: Discussionmentioning
confidence: 93%
“…A probable explanation for the higher values and the relatively stronger contamination of D2 in these plots could be the influence of soil micro-and mesoflora and micro-and mesofauna, erosion processes (Andrello and Appoloni, 2004) or differences in the initial cesium contamination before Chernobyl due to other sources. If we observe the plots from Central Balkan the tendencies in cesium profiles in plots PB1 and PB2 are quite similar and the content of cesium decreases clearly in depth.…”
Section: Discussionmentioning
confidence: 93%
“…This study used 137 Cs measurements to document soil erosion rates on well weathered tropical soils with sandy texture, at a latitude close to 20°S. Andrello and Appoloni (2004) also reported encouraging results when using 137 Cs to estimate rates of soil loss from more clayey subtropical soils in southern Brazil. Other studies reported by Bacchi et al (2003Bacchi et al ( , 2011 and Correchel et al (2006) have further confirmed the validity of the approach.…”
Section: Introductionmentioning
confidence: 84%
“…The average inventory of beryllium-7 was 211 Bq.m -2 with a spatial variability around of 23%. Andrello et al (2004b) presented spatial variability of cesium-137 in Londrina region as about 19%. Although, cesium-137 and beryllium-7 has different origin, the spatial variability represents the topographic, microtopographic and pluviometric variability of the region.…”
Section: Methodsmentioning
confidence: 94%